The Effectiveness of Electronic Modules on Problem-Solving Oriented Work and Energy Topics to Improve Student Learning Outcomes - Muhammad Andrean Lazuardi; Abdul Salam M; Surya Haryandi; Mohd Ali Ibrahim (Jurnal Ilmiah Pendidikan Fisika, 2023)
Technological developments make the education sector need to present modern learning resources while facilitating students in dealing with problems in the 21st century. Thus, the research aimed to develop an electronic module on the topic of work and energy-oriented to effective problem-solving so that it can be used to improve student learning outcomes. This research is in the form of development research using the ADDIE model. The subjects of this research were 33 students of X MIPA 4 SMA Negeri in Banjarmasin. The data analysis technique used is descriptive quantitative with a learning outcomes test as the research instrument used. The research results explained that the electronic module was declared highly effective with an N-gain score of 0.76. Thus, the electronic module physics on work and energy-oriented problem-solving are feasible to improve student learning outcomes.